Peningkatan Pemanfaatan Layanan BPJS Kesehatan melalui Edukasi dan Pendampingan Masyarakat di Fasilitas Kesehatan Tingkat Pertama - Syamdarniati; Anna Layla Salfarina; Raudatul Jannah; Baiq Ricca Afrida; Ni Putu Aryani (Insan Kreasi Media, 2026)
Digital transformation in healthcare services is an important strategy to improve access and quality of public healthcare services. However, the use of digital health applications still faces various obstacles, particularly related to the level of digital literacy of users. This study aims to analyze the effect of education on the use of the Mobile National Health Insurance (JKN) application on improving participants' knowledge and skills in accessing healthcare services independently. The study used a pre-experimental design with a one-group pretest-posttest approach involving 50 JKN participants selected using a purposive sampling technique. The variables measured included the level of knowledge and skills in using the Mobile JKN application before and after the educational intervention. Data were analyzed using descriptive analysis and the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed that the average knowledge score of participants increased from 62.4 to 84.7, while the average skill score increased from 58.1 to 86.3 after the intervention. The Wilcoxon test results showed a significant difference between the values ​​before and after education for the knowledge variables (p < 0.001) and skills (p < 0.001). These findings indicate that education on the use of the Mobile JKN application is effective in improving participants' ability to utilize digital health services. The research findings have important implications for the development of digital health literacy programs to support the transformation of technology-based health services and increase optimal utilization of JKN services.